2021
DOI: 10.3390/curroncol28050352
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil-to-Lymphocyte Ratio as a Predictive Marker of Response to Atezolizumab Plus Bevacizumab for Hepatocellular Carcinoma

Abstract: Background: Combination therapy with anti-programmed death-ligand 1 monoclonal antibody atezolizumab plus anti-vascular endothelial growth factor agent bevacizumab (Atezo/Bev) was approved in 2020 as a first-line treatment for unresectable hepatocellular carcinoma (HCC). Atezo/Bev therapy is relatively well tolerated; however, factors that can predict its response have not yet been reported. Thus, we aimed to investigate whether the pretreatment neutrophil-to-lymphocyte ratio (NLR) could predict the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…The third main finding of our study was that assessment by the EOB-MRI hepatobiliary phase affected PFS in the atezolizumab plus bevacizumab group (Figures 1 and 2). We also examined liver function and the neutrophil-to-lymphocyte ratio (NLR) that have been reported to be associated with PFS for atezolizumab plus bevacizumab therapy, but found no statistical differences [20,21]. One of the reasons for predicting therapeutic effects is that the heterogeneous and hyperintense types were present in a certain number of patients with HCC carrying β-catenin mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The third main finding of our study was that assessment by the EOB-MRI hepatobiliary phase affected PFS in the atezolizumab plus bevacizumab group (Figures 1 and 2). We also examined liver function and the neutrophil-to-lymphocyte ratio (NLR) that have been reported to be associated with PFS for atezolizumab plus bevacizumab therapy, but found no statistical differences [20,21]. One of the reasons for predicting therapeutic effects is that the heterogeneous and hyperintense types were present in a certain number of patients with HCC carrying β-catenin mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may have been due to the small number of cases in the current study. In addition, it should be noted that previously reported NLR cut-off values for predicting patient outcomes differ between studies [15, 43-45], and NLRs change due to various patient conditions (e.g., infections and certain medications, particularly steroid-based immunosuppressive regimens). Therefore, more robust NLR cut-off values are desirable for use in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As in the previous reports [41,42], readministration of lenvatinib after diagnosed disease progression during immunotherapies has the potential of disease control effect in some patients. Recently, other researchers reported the utility of NLRs for predicting patient outcomes following Atezo/Bev treatment of HCC [15,[43][44][45]. Furthermore, Maesaka et al [15] reported an NLR cut-off value of ≥3 as a useful predictor for HPD.…”
Section: Kawamura Et Almentioning
confidence: 99%
“…Chuma et al reported that ATZ + BV treatment might offer significant benefits in patients who meet the IMbrave150 trial or have a low NLR [ 31 ]. Eso et al reported that pretreatment NLR might be a useful predictive factor associated with the therapeutic response [ 32 ]. NLR is a marker of systemic inflammatory response and reflects the balance between the neutrophils and lymphocytes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%